Influence of wastewater type on the distribution of microbial community compositions including pathogenic bacteria within wastewater treatment processes - Bokjin Lee; Sang-Hoon Lee; Jaiyeop Lee; Na-Kyung Kim; Ilho Kim; Saerom Park; Seogku Kim; So-Young Ham; Hee-Deung Park; Dongbeom Im; Han-Shin Kim (Sustainable Environment Research)
Abstract Many wastewater treatment plants (WWTPs) utilize biological processes to remove organic matter using microbial communities. The present study elucidates the distributions of microbial communities and potential pathogenic bacterial compositions from influent, activated sludge, and effluent of secondary clarifier samples from 10 WWTPs treating municipal (n = 5), hospital (n = 2), and livestock (n = 3) wastewater using 16S rRNA high-throughput amplicon sequencing. Despite the regional differences in location, similar microbial community compositions and pathogenic bacteria distributions were observed from WWTPs treating the same wastewater type. The highest operational taxonomic unit richness, phylogenetic diversity, and evenness were found in municipal WWTPs. Redundancy analysis showed that the concentration of phosphate significantly influences the abundance of pathogenic bacteria in WWTPs. The phylum Proteobacteria (37–68%) was the most dominant bacteria across all samples. Corynebacterium and Pseudomonas were the dominant potential pathogenic bacteria in livestock and municipal WWTPs; the two hospital WWTPs had Klebsiella and Pseudomonas as the dominant genera. The presence of pathogenic bacteria across multiple WWTP locations and wastewater types indicates the need for in-depth monitoring in various stages of wastewater treatment processes as well as in discharged wastewater.